Uso de energia microondas na síntese de enonas e de 4,5-diidropirazóis trialometil-substituídos - Beck, Paulo Henrique (2007)
The solvent-free microwave-assisted regiospecific synthesis of a series of 5-trihalomethyl-4,5-dihydro-1H-pyrazole (7 - 10) from the cyclocondensation of 1,1,1- trihalo-4-alkoxy-3-alken-2-ones (5 - 6),[ CX3COC(R)2=C(R)1OR, where X = Cl, F; R = Me, Et; R2 = H, Me and R1 = H, Me, Et, Pr, iso-Pr, Bu, iso-Bu, tert-Bu, iso - Pen, Ph, 4-Me-Ph, 4-MeO-Ph, 4-NO2-Ph, 4-Cl-Ph, 4-Br-Ph, 4-F-Ph, H, OEt,] with carboxymethyl hydrazine or pentafluorophenyl hydrazine is described. The reaction was performed in a 1:1.2 molar ratio of alken-2-ones and hydrazine, in a single reaction step, for 6-12 minutes, in good yields (70-98%). The advantages obtained by using microwave irradiation under solvent-free conditions, rather than a conventional method, were also demonstrated. The 4-alkoxy-1,1,1-trihalo-3-alken-2-ones (4-5) were obtained from the reaction of cloreto de trichloroacetyl cloride or trifluoroacetic anhydride with enol ethers or acetals in presence of pyridine, solvent free and microwave induced techniques.